Role of government financial support and vulnerability characteristics associated with food insecurity during the covid-19 pandemic among young peruvians - Curi-Quinto K. (2021)
Funding: This research was funded by PROCIENCIA (CONCYTEC/FONDECYT), the British Embassy, the MRC grant (MR/S024778/1) and Newton Fund, grant number 030-2019.